Biodiesel from adsorbed waste oil on spent bleaching clay using CaO as a heterogeneous catalyst - Boey, Peng-Lim; Maniam, Gaanty Pragas; Abd Hamid, Shafida (EuroJournals Publishing, Inc., 2009)
Oil-laden spent bleaching clay (SBC) is currently under-utilized by dumping it in landfills without any attempt to recover the oil. Therefore, effort has been made to extract the waste oil using different solvents (methanol, ethanol, petroleum ether, and hexane), and utilize the oil in transesterification reaction. Cleaner oil (free from polar components and least acid content) of 28.2 ± 0.6 wt.%, a significant amount susceptible to be converted to biodiesel, was extracted using non-polar solvent. However, the relatively high free fatty acid content leads to yield loss through saponification under homogeneous base-catalyzed reaction. As such, in the present work, heterogeneous base-catalyzed transesterification has been proposed using CaO. Parametric study has been conducted and the optimal conditions was found to be: methanol/oil mass ratio 0.5:1; catalyst amount 6 wt.%, and reaction temperature of 65°C. The highest purity of 98.6 ± 0.8 % was achieved within 2.5 h. Biodiesel yield under the solid catalyst was quantified as 90.4% as compared to 45.5% and 61.0%, respectively for classical NaOH, and KOH homogeneous catalysts.